Environmental regulation and industry location - Abay Mulatu; Reyer Gerlagh; Dan Rigby; Ada Wossink (Fondazione Eni Enrico Mattei (FEEM), 2009)
This paper estimates the effect of environmental regulation on industry location and compares it with other determinants of location such as agricultural, education and R&D country characteristics. The analysis is based on a general empirical trade model that captures the interaction between country and industry characteristics in determining industry location. The Johnson-Neyman technique is used to fully explicate the nature of the conditional interactions. The model is applied to data on 16 manufacturing industries from 13 European countries. The empirical results indicate that the pollution haven effect is present and that the relative strength of such an effect is of about the same magnitude as other determinants of industry location. A significant negative effect on industry location is observed only at relatively high levels of industry pollution intensity.
Keywords: O14; 330; Pollution Haven Hypothesis; Comparative Advantage; Industry Location